Processos educativos baseados em cognição distribuída voltados a experiências de inteligência coletiva com tecnologias da cibercultura - Costa, Pablo João Canal da (2021)
This study explores distributed cognitive processes in the context of networks and driven by elements of collective intelligence, typical of the cyberculture area. In it, we use the theoretical approach of distributed cognition together with the concept of collective intelligence, establishing relationships with authors who help to elucidate such processes. We take as a guide the following question: what is the potential of the use of digital technologies proper of cyberculture, in the promotion of processes of distributed cognition, aiming at experiences of collective intelligence? The study is exploratory and adopts participant research as procedure. It was chosen to work with a focal group constituted by 5 students of the 8th grade of Elementary School of a Municipal public school in the city of Passo Fundo - RS, Brazil - who were taking Mathematics lessons. The focal group classes brought robotics elements linked to mathematical concepts, through collaborative activities with the use of digital mind maps. The research aimed to verify the potential of the use of digital technologies in collaborative activities in the educational context of Hybrid Learning, to produce an experience of collective intelligence, based on the theory of distributed cognition. Online and face-to-face activities were developed using different digital technologies, among them the collaborative mind map. The conclusion was reached that digital technologies, typical of cyberculture, can contribute to the mobilization of distributed cognition processes in order to provide collective intelligence experiences. It is highlighted that the quality of distributed cognition processes depends on human, technological and environmental resources suitable to achieve this goal.